Fruit Metabolism and Metabolomics - Moing, Annick; Osorio, Sonia; Pétriacq, Pierre (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Over the past ten years, metabolomics strategies have allowed the relative or absolute quantitation of metabolite levels for the study of various biological questions in plant sciences. For fruit studies, in particular, they have participated in the identification of the genes underpinning fruit development and ripening. This book proposes examples of the current use of metabolomics studies of fruit for basic research or practical applications. It includes articles about several tropical and temperate fruit species. The studies concern fruit biochemical phenotyping, fruit metabolism during development and after harvest, including primary and specialized metabolisms, or bioactive compounds involved in fruit growth and environmental responses. The analytical strategies used are based mostly on liquid or gas chromatography coupled with mass spectrometry, but also on nuclear magnetic resonance and near-infrared spectroscopy. The effect of genotype, stages of development, or fruit tissue type on metabolomic profiles and corresponding metabolism regulations are addressed for fruit metabolism studies. The interest in combining other omics with metabolomics is also exemplified.